2010
DOI: 10.1128/mcb.01625-09
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-Wide RNA Interference Screen Identifies a Differential Role of the Mediator CDK8 Module Subunits for GATA/ RUNX-Activated Transcription in Drosophila

Abstract: Transcription factors of the RUNX and GATA families play key roles in the control of cell fate choice and differentiation, notably in the hematopoietic system. During Drosophila hematopoiesis, the RUNX factor Lozenge and the GATA factor Serpent cooperate to induce crystal cell differentiation. We used Serpent/ Lozenge-activated transcription as a paradigm to identify modulators of GATA/RUNX activity by a genomewide RNA interference screen in cultured Drosophila blood cells. Among the 129 factors identified, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 71 publications
3
35
3
Order By: Relevance
“…In particular, studies in the fruit fly suggested a functional separation of Cdk8 and Med12 in regulating key developmental genes. 37,62 In agreement with these findings our study suggests that Med12 fulfills an important role in silencing developmental genes together with PRC1. Notably, apart from its repressive function, Med12 also keeps the ES self-renewal network active.…”
Section: Discussionsupporting
confidence: 81%
“…In particular, studies in the fruit fly suggested a functional separation of Cdk8 and Med12 in regulating key developmental genes. 37,62 In agreement with these findings our study suggests that Med12 fulfills an important role in silencing developmental genes together with PRC1. Notably, apart from its repressive function, Med12 also keeps the ES self-renewal network active.…”
Section: Discussionsupporting
confidence: 81%
“…This result contrasts previous results examining the kinase module that found Med13 was stable upon loss of Med12 (16,17). To confirm our findings, we repeated the experiment with dsRNA directed against both Med12 and Med13.…”
Section: Resultscontrasting
confidence: 56%
“…This contrasts the findings in Drosophila Kc cells (16) and in imaginal discs in vivo (17) where Med13 is stable upon loss of Med12. One possible explanation is the presence of a gene product that can substitute for Med12 in Kc cells and imaginal discs that is not present in S2 cells.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…22 Third, in a genome wide RNAi screen, dMLF scored as a potential co-activator of LZ. 23 Further analysis revealed that mlf participates in a positive feedback loop to control the activity of LZ. 24 Indeed, dMLF expression is activated in the crystal cell lineage by LZ and required for stabilizing LZ, thereby contributing to the fine-tuning of crystal cell number.…”
Section: Mlf Functions In Mammalsmentioning
confidence: 99%